Metal–Organic Frameworks Derived Plasmonic Catalyst with Full Spectral Response for Photoelectrochemical Water Splitting Enhancement. Issue 5 (12th May 2022) - Li, Chuanping; Li, Shuoren; Hang, Tianxiang; Guo, Feifei; Zhu, Xian-Dong; Liu, Tian-Fu
Abstract : Plasmonic Photoelectric Catalysts In article number 2100071, Xian‐Dong Zhu, Tian‐Fu Liu, and co‐workers construct a plasmon‐enhanced catalyst by integrating metal–organic frameworks (MOFs)‐derived Cd0.8 Zn0.2 S with Ag/Au hollow porous nanoshells (Ag/Au HPNSs). The catalyst exhibits wide spectral absorption and photoelectrochemical water oxidation ability due to the synergistic effect of surface plasmon resonance of Ag/Au HPNSs and large specific surface area of porous Cd0.8 Zn0.2 S.